Study on Group Differences in Migrant Workers’ Urban Integration in China - Li, Haibo; Li, Haitao; Guo, Shengyu; Fan, Xuelong; Liu, Feiyue (Frontiers in Integrative Neuroscience, 2022)
Objectives: This paper evaluates and tests the group differences of migrant workers' urban integration from the perspectives of individual characteristics and migration characteristics, so as to provide theoretical support and practical guidance for the government to issue more effective assistance policies. Methods: AHP evaluation method and entropy method are used to calculate the urban integration level of migrant workers, One-Way Analysis of Variance and Optimal Scaling Regression are used to test the group differences of migrant workers' urban integration. Results: Based on the questionnaire data of 854 migrant workers of China, The scale of migrant workers' urban integration has good reliability and validity. The overall level of migrant workers' urban integration is 49.61%. There are group differences in migrant workers' urban integration. The impact of education level ,income level and migration time on migrant workers' urban integration is significantly positive. The impact of migration distance on migrant workers' urban integration is significant negative. The urban integration level of migrant workers who have family members accompanying them is higher than that of migrant workers who have no family members accompanying them. Gender, Age and Marriage have no significant impact on migrant workers' urban integration. Strengths and limitations of this study：This study aims to measure and test the group differences of migrant workers' urban integration by using Analysis of Variance and Optimal Scaling Regression. However, the shortcomings of this study are: Selection of "migrant workers' urban integration" scale, and the representativeness of the sample used in this study. Conclusions: There are group differences in migrant workers' urban integration with different education level, income level, migration distance, migration time and status of family members accompanying. In the policy of promoting migrant workers' urban integration, we should accurately count the characteristics of migrant workers, and give more attention to migrant workers with low education level, low income level, long migration distance, short migration time and without family accompanying.